2020
DOI: 10.26719/emhj.20.130
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with worse outcomes in COVID-19: a retrospective study in Saudi Arabia

Abstract: Background: The rapid emergence of the novel coronavirus disease 2019 (COVID-19) has resulted in millions of infected patients and hundreds of thousands of deaths worldwide. Health care services delivery is being compromised due to the surge in the number of infected patients during this pandemic. Aims: This study aimed to assess the risk factors associated with poor prognosis among COVID-19 patients in Saudi Arabia. Methods: This was a multi-centre retrospective cohort study that included all laboratory-confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 17 publications
7
52
1
4
Order By: Relevance
“… 50 Reportedly, SARS-CoV-2 has negatively influenced the outcome of anemic patients by interacting with hemoglobin either by attacking heme group on 1-beta chain leading to hemolysis or by hepcidin-mimetic action of a spike protein causing hyperferritinemia. 65 , 66 Cardiac and chronic respiratory diseases have also been identified as risk factors associated with worse outcomes in COVID-19 patients 67 while lung and chronic kidney diseases were also recorded as risk factors in an independent study. 68 We also observed that neurological comorbidities contribute significantly to mortality among the hospitalized patients in line with some previous studies which reported cerebrovascular diseases leads to severe outcomes in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Reportedly, SARS-CoV-2 has negatively influenced the outcome of anemic patients by interacting with hemoglobin either by attacking heme group on 1-beta chain leading to hemolysis or by hepcidin-mimetic action of a spike protein causing hyperferritinemia. 65 , 66 Cardiac and chronic respiratory diseases have also been identified as risk factors associated with worse outcomes in COVID-19 patients 67 while lung and chronic kidney diseases were also recorded as risk factors in an independent study. 68 We also observed that neurological comorbidities contribute significantly to mortality among the hospitalized patients in line with some previous studies which reported cerebrovascular diseases leads to severe outcomes in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The results from a multi-center, retrospective, cross-sectional study, performed from March 1, 2020, to March 31, 2020, across all parts of the country, revealed a high percentage of diabetes among the COVID-19 positive patients (from the 220 reported comorbidities, 83 had diabetes) [ 29 ]. From a retrospective study in March 2020 done on 648 COVID-19 patients in healthcare facilities across all parts of Saudi Arabia, 73 (11.3 %) COVID-19 patients were found to have diabetes [ 30 ]. In another retrospective, a single-center study was performed at Al Noor Specialist Hospital, Mecca, using 150 COVID-19 patients (from March 12 to 31 of 2020).…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…Around 170 million confirmed cases and more than 3.54 million deaths were registered worldwide, with a Case Fatality Rate (CFR) of 2 as of May 31, 2020, [5]. In the same time interval, the Kingdom of Saudi Arabia has registered a lower CFR 1.7 similar to the international clinical manifestation and risk factors of COVID-19 [6,7,8].…”
Section: Introductionmentioning
confidence: 99%